1996
DOI: 10.1172/jci118485
|View full text |Cite
|
Sign up to set email alerts
|

Specific detection of hepatitis C virus minus strand RNA in hematopoietic cells.

Abstract: The presence of hepatitis C virus (HCV) negative strand RNA in extrahepatic compartments based on PCR detection assays has been suggested in many reports with a very heterologous detection rate (from 0 to 100%). In this study, we have analyzed the presence of HCV negative strand in hepatic (liver biopsies, n ϭ 20) and extrahepatic (sera, n ϭ 32; PBMC, n ϭ 26 and fresh bone marrow cells, n ϭ 8) compartments from infected patients with three different reverse transcriptase (RT)-PCR-based assays using primers loc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
190
0
5

Year Published

1998
1998
2008
2008

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 260 publications
(201 citation statements)
references
References 36 publications
6
190
0
5
Order By: Relevance
“…Indeed, the possibility still exists that the detection of the negativestranded HCV RNA is an artifact caused by the high titer of positive-stranded HCV RNA in the sample. 53 In this experiment, the titer of positive sense HCV RNA at 4, 5, and 14 weeks posttransfusion were 10 7 ,10 6 , and 10 6 , respectively. However, a strong band was detected only at 5 weeks posttransfusion in spite of the lower titer than that at 4 weeks posttransfusion.…”
Section: Discussionmentioning
confidence: 68%
“…Indeed, the possibility still exists that the detection of the negativestranded HCV RNA is an artifact caused by the high titer of positive-stranded HCV RNA in the sample. 53 In this experiment, the titer of positive sense HCV RNA at 4, 5, and 14 weeks posttransfusion were 10 7 ,10 6 , and 10 6 , respectively. However, a strong band was detected only at 5 weeks posttransfusion in spite of the lower titer than that at 4 weeks posttransfusion.…”
Section: Discussionmentioning
confidence: 68%
“…To assess the active replication of HCV demonstrated by the detection of negative sense molecules, and to avoid false-positive results caused by the lack of specificity of the techniques using primers from the 5Ј-noncoding region, reverse transcription and amplification of negative-strand templates were performed using capsid-derived specific primers, according to recent reported findings. 21 cDNAs were synthetized with specific primer CAP 3 (the samples were heated at 100°C for 1 hour before the PCR), and amplified with the outer primers during the first PCR: CAP 3 (5Ј TGT TGC CGC GCA GGG GCCC 3Ј) (position 448-466) and 185 (5Ј CCG CAC GTA GGG TAT CGA TGA C 3Ј) (position 732-751), then with the inner primers during the second PCR: CAP 4 (5Ј AGG TTG GGT GTG CGC GCG 3Ј) (position 468-485) and 186 (5Ј ATG TAC CCC ATG AGG TCG GC 3Ј) (position 705-728). The expected size of the amplification product is 260 bp.…”
Section: Methodsmentioning
confidence: 99%
“…This result agrees with previous observations from the literature that showed that self-priming of HCV RNA leads to false-positive results for HCV-RNA negativestrand detection mostly in patient samples with a high viral load. 21 Serial Inoculations. To perform the ''blood passage,'' blood samples were taken from 2 mice (injected with ALL cells in 1 case and with PBMC from a patient with chronic hepatitis C in the other case) at the moment of their killing, and then were reinjected subsequently into 2 other mice.…”
Section: Hcv-rna Negative-strand Detection In Circulating Cells Isolatedmentioning
confidence: 99%
“…Numerous publications have analyzed extrahepatic compartments of viral replication that could potentially contribute to plasma viremia, most frequently peripheral blood mononuclear cells (PBMC). [7][8][9][10][11][12][13][14] The contribution of PBMC-based HCV replication to total viremia remains unclear, however, as the level of negative-strand HCV RNA in PBMC is very low with respect to that in liver. [15][16][17][18] The continued presence of viral RNA in the PBMC of subjects who had either spontaneously cleared their plasma viremia or cleared viremia following antiviral therapy has recently been reported, raising concerns that PBMC may serve as a long-lived HCV reservoir capable of rekindling systemic infection.…”
mentioning
confidence: 99%